2017
DOI: 10.1002/ente.201700569
|View full text |Cite
|
Sign up to set email alerts
|

Hexafluoroisopropanol as a Low‐Boiling Extraction Solvent for 5‐Hydroxymethylfurfural Production

Abstract: In this study, we show that the fluorous alcohol hexafluoroisopropanol (HFIP) can act as a superior solvent for the in situ extraction of 5‐hydroxymethylfurfural (HMF) from an aqueous reaction system. HFIP has a far higher partition coefficient for HMF than common extraction solvents such as methyl isobutyl ketone (MIBK) and n‐butanol and has a significantly lower boiling point of 58–59 °C. In a system containing fructose, HCl as the catalyst, and HFIP as the extraction solvent, a high HMF yield of 89 % is ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…[229] In 20 min residence time, a full fructose conversion with 76 % HMF yield was obtained at 100°C and 20 bar. [234] The synthesis of furfural from xylose has been performed in a biphasic water-butanol packed bed milli-reactor made of zirconium (d C = 8 mm) ( Table 4, entry 15). [234] The synthesis of furfural from xylose has been performed in a biphasic water-butanol packed bed milli-reactor made of zirconium (d C = 8 mm) ( Table 4, entry 15).…”
Section: Heterogeneously Catalyzed Furan Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[229] In 20 min residence time, a full fructose conversion with 76 % HMF yield was obtained at 100°C and 20 bar. [234] The synthesis of furfural from xylose has been performed in a biphasic water-butanol packed bed milli-reactor made of zirconium (d C = 8 mm) ( Table 4, entry 15). [234] The synthesis of furfural from xylose has been performed in a biphasic water-butanol packed bed milli-reactor made of zirconium (d C = 8 mm) ( Table 4, entry 15).…”
Section: Heterogeneously Catalyzed Furan Synthesismentioning
confidence: 99%
“…HFIP is a low boiling point solvent and hence facilitates the distillative retrieval of HMF after its production. [234] The synthesis of furfural from xylose has been performed in a biphasic water-butanol packed bed milli-reactor made of zirconium (d C = 8 mm) ( Table 4, entry 15). [230] The reaction was catalyzed over watertolerant H 3 PO 4 modified hydrated tantalum oxide catalysts.…”
Section: Heterogeneously Catalyzed Furan Synthesismentioning
confidence: 99%
“…In a recent publication, [52] it has been shown that hexafluoroisopropanol, a low‐boiling extraction solvent, has a partition coefficient superior to solvents such as MIBK or n ‐butanol. The easy isolation of HMF, the good selectivity, and easy recyclability are clear advantages of this solvent.…”
Section: More Recent Process Development For Hmf Production (2006 To ...mentioning
confidence: 99%
“…(2-butanol) = 100 °C) lead to difficulties in HMF production and isolation. In previous investigations we showed that hexafluoroisopropanol (HFIP, Scheme 2 ) solves these problems in an excellent way [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%